Identification of contractors claims in Turnkey projects according to FIDIC by the system dynamics method (Case study on the 7008 housing units building project in Ojeda, Venezuela) - Amir Momeni; Elham Rastar; Armin Monirabbasi (مهندسی و مدیریت ساخت)
In this study, contractor’s claim and its management in in turnkey contracts according to FIDIC has been discussed through library studies and surveys among experienced specialists in international civil projects and then this discussion has been developed with benefit of modeling the claim using system dynamics and its evaluattion on a case study as well as relying on opinions of experts.As a result of modeling the claims of contractors in in turnkey contracts according to FIDIC, the most important variables and parameters affecting or affected the claims, their intensity and type of relationship with each other was determined in this contracts.The results show that modeling by system dynamics method is very useful for qualitative and quantitative analysis of the contractor’s claims.can be admitted the most important factors affect the claims of contractors in turnkey contracts according to FIDIC that 75% of them are financial claims are the delays of employer payments with a share of about 60% , project changes with a share of nearly 20% and both are under the influence of strategies and management procedures, Also their intensity will be increased in force majeure situations and unexpected events, Moreover, The lack of project management system and risk allocation and not having got of ownershipflotationon the project scheduledisturbance in process of managing the claims of contractors in Turnkey contracts according to FIDIC.